(untitled) (Andamios, Revista de Investigación Social, 2015)
In this work, part of an ethnographic research on greater spatial and territorial phenomena, there is a discussion on some processes of change that occur in the Chilean Patagonia, which corresponds to one of the few places in the world where there is unoccupied land and a fountain of resources demanded by the global economy. It is identified as a place not yet contaminated, with important biodiversity, rivers flow freely and have great energy potential; remote, slightly accessible, with inhabitants isolated and distanced, with poor services product of the centralism of the national State. It has identified different actors and imageries that are generating a rewriting of the territory with distinct and contradictory purposes such as the State, the capital, communities, environmental groups, migrants by change of lifestyle and others with ideological interests. The recognized factors cause the acceleration of time and alter the conditions of life in the traditional which is considered the last frontier of capitalism.